2015
DOI: 10.2217/fon.15.153
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Access Palliative Radiation Therapy Programs: An Efficient Model of Care

Abstract: Palliating symptoms of advanced and metastatic cancers are one of the most common indications for radiation therapy (RT), and the demand for palliative RT is increasing. Dedicated rapid access palliative RT programs improve access to care, and can deliver RT in a more efficient and evidence-based manner than standard RT programs. In this narrative review, we discuss the role of palliative RT in comprehensive cancer care, and challenges that have faced patients trying to access it. We describe how rapid access … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…In Start date of palliative radiotherapy addition, although the median of 6 days from the decision to treat date to the start of palliative radiotherapy for our study patients is comparable with the median of 7 days (range 0e123) for all patients with cancer from our province treated with palliative radiotherapy at TOH from 2016 to 2018, the time from biopsy to the start of radiotherapy in our study was about 20 days, with international guidelines again recommending 14 days from diagnosis to treatment for lung cancer patients [14]. Rapid access palliative radiotherapy programmes have been shown to improve access to care, while delivering more timely and efficient treatment in several settings worldwide [17]. Exploring the development of a similar model for the Inuit population from Nunavut may help to streamline their clinical pathway even further.…”
Section: Discussionmentioning
confidence: 65%
“…In Start date of palliative radiotherapy addition, although the median of 6 days from the decision to treat date to the start of palliative radiotherapy for our study patients is comparable with the median of 7 days (range 0e123) for all patients with cancer from our province treated with palliative radiotherapy at TOH from 2016 to 2018, the time from biopsy to the start of radiotherapy in our study was about 20 days, with international guidelines again recommending 14 days from diagnosis to treatment for lung cancer patients [14]. Rapid access palliative radiotherapy programmes have been shown to improve access to care, while delivering more timely and efficient treatment in several settings worldwide [17]. Exploring the development of a similar model for the Inuit population from Nunavut may help to streamline their clinical pathway even further.…”
Section: Discussionmentioning
confidence: 65%
“…Consequently, patients’ access to quality care and an improved quality of life is made possible. [ 3 19 ] The other advantage provided using TomoTherapy MV CT in conjunction with a TomoTherapy linear accelerator for palliative treatment is that as in this procedure; the patient is both scanned and treated on the same TomoTherapy couch, the accuracy in reproducing the patient's position from scanning to treatment delivery can be greatly improved.…”
Section: Discussionsmentioning
confidence: 99%
“…In contrast, the conventional planning workflow usually requires at least 1-day turnaround. As studies have shown that dedicated rapid access palliative radiation therapy improves patients’ access to care,[ 3 ] the quick access to radiation therapy, and the rapid workflow will potentially improve these patients’ quality of life significantly; Better reproducibility in patient positioning from simulation to treatment, as the patient is simulated and treated on the same unit. The turnaround time from simulation to treatment is also greatly reduced; and For less-mobile palliative patients, it is possible to allow the patient to stay on the TomoTherapy couch from simulation until treatment, which minimizes the chance of doing damage to the patients and reduces reduced potential aggravating morbidity pain during bed transfer.…”
Section: Onclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, dedicated PRT programs, such as the Rapid Response Radiotherapy Program in Toronto and the Supportive and Palliative Radiation Oncology service in Boston, have demonstrated improved quality of care for patients being urgently evaluated for PRT. 19 Following management of pain and neurologic symptoms, clinicians were faced with managing fatigue in nearly half of the patients (49%). e prevalence of fatigue among cancer patients and its impact on quality of life 20 highlight the need for this key symptom to be addressed throughout the continuum of cancer care.…”
mentioning
confidence: 99%